On the leading edge of patient care practical updates in GI and hepatology : (American Gastroenterological Association, 2001)
The course syllabus provides comprehansive details of each lecture and clinical challenge session. Some chapters contain the presenter's slide materials; others have provided detailed text expanding on the topic.